Dinâmica da desigualdade salarial no Brasil e o papel de determinantes para além da qualificação dos trabalhadores - Procópio, Igor Vieira,Freguglia, Ricardo da Silva,Corseuil, Carlos Henrique,Guedes, Fillipe (Instituto de Pesquisa Econômica Aplicada, 2022)
The aim of this paper is to evaluate the evolution of wage inequality components in Brazil, specifically the evolution of the return to unobserved skills, in the period of 2003 to 2013. We use a method similar to that proposed by Cortes e Hidalgo-Pérez (2015), based on a hypothesis of invariance of the dispersion of unobserved skills for a group of workers who remain employed between two consecutive years. We incorporated two rules into this method. First, we allowed the evolution of wage inequality to be affected by unobservable characteristics of firms. Second, it considers different sets of workers for whom the hypothesis of invariance of the dispersion of skills not observed between two consecutive years would apply. Our results obtained from Rais-Identified data show that the first extension affects the results, which are robust to the alternatives considered for the second extension of the method. The results of our preferred specification point to a growth in the return (price) to unobserved skills, much more intense than what occurs without considering the influence of unobservable characteristics of firms on workers’ wages.
10.38116/td2733
Keywords: Graue Literatur; wage inequality; unobserved skills; return to skills